2020
DOI: 10.21037/jtd-20-2111
|View full text |Cite
|
Sign up to set email alerts
|

Association of stress hyperglycemia ratio with intracoronary thrombus burden in diabetic patients with ST-segment elevation myocardial infarction

Abstract: Background: Large intracoronary thrombus burden is not rare during primary percutaneous coronary intervention (PCI) in patients with acute ST-segment elevation myocardial infarction (STEMI). Stress hyperglycemia is independently associated with poor prognosis. However, the underlying relationship between stress hyperglycemia and thrombus burden remains unknown. This study aims to investigate the association of stress hyperglycemia, evaluated by the combination of acute and chronic glycemic levels, with intraco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
(44 reference statements)
0
24
0
Order By: Relevance
“…A number of studies in both ischemic stroke and other patient cohorts are consistent with this. 12,[14][15][16][17]21,22 Future interventional studies need to acknowledge and incorporate this in their design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies in both ischemic stroke and other patient cohorts are consistent with this. 12,[14][15][16][17]21,22 Future interventional studies need to acknowledge and incorporate this in their design.…”
Section: Discussionmentioning
confidence: 99%
“…threshold of 1.19 best distinguished between large or small thrombus burden in diabetic patients with STsegment elevation myocardial infarction. 16,17 In light of the results from the SHINE study 13 and the emerging role of SHR and GG to accurately reflect the presence of SIH, it is important to assess stroke outcome against specific biomarkers of SIH other than glucose. This study investigated the relationship between SHR and GG with stroke outcome at hospital discharge, both as continuous variables and at nominated thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Elevated stress hyperglycemia level may contribute to the formation of intracoronary thrombus and has been identified as a better predictive value than admission blood glucose levels. [29] Strategies to balance ischemic events and bleeding complications still require further investigation. [30] Similarly to previous studies [17,18], our results showed that cardiogenic shock was more common in DM and transient hyperglycemia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acute fluctuations in glucose levels are associated with increased plaque instability, infarct size, and worse heart function (26), which may also lead to worse prognosis. Also, recent studies reported that stress hyperglycemia was positively associated with in intracoronary thrombus burden and no-reflow phenomenon, which may further explain the significantly higher incidence of mortality and cardiogenic shock in high SHR group (27,28).…”
Section: Discussionmentioning
confidence: 92%